A New Chief Editor for Neural Plasticity Growth - Michel Baudry (Neural Plasticity)
Neural Plasticity is pleased to announce the appointment of Dr. Michel Baudry as its new Chief Editor. Dr. Baudry is currently University Professor at Western University of Health Sciences in Pomona, CA. In this Editorial, Dr. Baudry describes some of the journal's journey and current status, and shares his vision and aspirations for its future.